The Effect of Financial and Non-Financial Compensation on Employee Performance During Covid-19 - Dody Kurnia; Sheila Azizah; Andre Suhendra (Almana : Jurnal Manajemen dan Bisnis, 2020)
The 2019 coronavirus pandemic (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Positive cases of COVID-19 began to be found in Indonesia on March 2, 2020. Now it has spread to 34 Provinces in Indonesia with DKI Jakarta, East Java, and Central Java as the most exposed provinces. To date, there are 287,008 positive cases in Indonesia, 214,947 people recovered from Covid-19, and 10,740 died. The impact of Covid-19 also has an impact on the banking sector, including Islamic banking in Indonesia. Bank BJB Syariah is one of the banks that experienced the impact during the COVID-19 pandemic. BJBS is facing a decrease in organizational productivity to employee performance. The purpose of this study was to determine the effect of financial and non-financial compensation on employee performance during COVID-19. This type of research is a quantitative method with a population of 231 people and a sample of 149 respondents. The data analysis technique used is multiple linear regression analysis. The results showed that the financial and non-financial compensation variables had a significant effect on employee performance at BJB Syariah Head Office.